2020
DOI: 10.1111/resp.13945
|View full text |Cite
|
Sign up to set email alerts
|

Probe‐based confocal laser endomicroscopy for pleural malignancies diagnosis

Abstract: Probe based confocal laser endomicroscopy (pCLE) is an optical imaging tool allowing live imaging of tissues at a cellular level. It remains experimental but its clinical value as a diagnostic/guiding tool is apparent. To address the lack of data in thoracic oncology and pleural diseases, we show the ability of pCLE during medical thoracoscopy to distinguish benign from malignant pleural involvement. See related Editorial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In comparison with 105 pleural biopsies, distinctive CLE patterns for pleural tumour deposits, malignant infiltration in fat tissue and benign fibrotic pleural tissue were validated with moderate interobserver agreement [ 61 ]. The most extensive experience, however, was gained recently by performing pCLE-imaging during thoracoscopic procedures [ 62 ▪ ]. Of the 62 included patients, 36 had benign and 26 had malignant pleural disease upon histological evaluation.…”
Section: Confocal Laser Endomicroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with 105 pleural biopsies, distinctive CLE patterns for pleural tumour deposits, malignant infiltration in fat tissue and benign fibrotic pleural tissue were validated with moderate interobserver agreement [ 61 ]. The most extensive experience, however, was gained recently by performing pCLE-imaging during thoracoscopic procedures [ 62 ▪ ]. Of the 62 included patients, 36 had benign and 26 had malignant pleural disease upon histological evaluation.…”
Section: Confocal Laser Endomicroscopymentioning
confidence: 99%
“…Several studies performed CLE-imaging for the diagnosis of pleural malignancies [60][61][62][63]. One study performed both pCLE and nCLE-imaging of the pleura during 20 diagnostic procedures, including thoracoscopy, surgical excision, ultrasound and endoscopic ultrasound [61].…”
Section: Pleural Malignancymentioning
confidence: 99%
“…Bonhomme et al . reported 2 in a publication in Respirology the use of probe‐based confocal laser endomicroscopy (pCLE) during pleuroscopy as part of their stepwise effort to establish the usefulness of pCLE in guiding pleural tissue sampling. In 62 patients (26 with malignant pleural diseases), they demonstrated that pCLE could be used with pleuroscopes and, in selected cases, provided impressive detailed cellular images comparable to eventual histological pictures from pleural biopsies at the same site.…”
mentioning
confidence: 99%